Embracing AI in higher education: redefining the role of lecturers - Mohd Rick, Abd Malik; Noradzan, Haslinda; Wan Ghani, Wan Aryati; Mohd Isnani, Zaidatulhusna (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Artificial Intelligence (AI) is increasingly used by university students for writing, coding, presentations, and problem-solving, but it poses challenges for lecturers to ensure responsible use that supports meaningful learning. While AI can assist in tasks, it cannot replace lecturers’ experience, pedagogical knowledge, and values. Universities and educators play a crucial role in guiding students to use AI ethically and as a tool for growth rather than a shortcut that undermines learning.